Notions and evaluation practices based on the approach for competences implemented in the Professional Technical Colleges of Costa Rica - Camacho Calvo, Silvia (2020)
The analysis on the educational modalities by competences creates a research area, the present theoretical - methodological exploration is oriented towards the analysis and reflection around the processes of teaching and learning, notions and evaluative practices in the implementation of the competency-based approach in Professional and Technical High Schools in Costa Rica. The research begins with a brief critical analysis on the notions, the curriculum and the evaluative practices under the competency-based approaches, to then contrast them with those generated in the Costa Rican context under the modality of the Education based on Labor Competency Standards (EBNC), implemented by the Ministry of Public Education of Costa Rica. To answer the research question a narrative was constructed, these includes the critical analysis of the theoretical, teachers and student discourses about the notions of competence and the evaluation practices in the EBNC, the analysis took place between 2015 and 2016. The aim was to put in perspective the need for an education that integrates the different aspects of knowledge and that transcends the emphasis of the labor skills towards an education that allows to develop the knowledge of how to live in the world as an active citizen, and where, in addition, diversity is recognized as a construction of significance of different worldviews, in the sense of interpretation horizons proposed by the hermeneuts, that is, to give meaning as a human being of the daily experiences of the actors in the educational system within the learning processes.